The Impact Of Religious Values On Social And Political Change In Tolitoli In The Early 20th Century - Abdul Latief, Juraid (International Journal of Educational Research & Social Sciences, 2022)
There is no doubt, interpretation of religious values by social and political elites in the modern social history has significantly influenced the development of political structure at national, regional and global level. At least, the phenomena has appeared since the period of Muhammad in the seventh century around Arabic peninsula, the rise of Islamic empires in the western Asia from the seventh to twelfth century, Spain under the Moslem and Christian powers, Turk during the Ottoman Empire from fifteenth to nineteenth century, Europe nations in the period of Crusaders from eleventh to fourteenth century, American independence war more than two hundred years ago. And in some cases, religious values were used effectively to mobilize local people against the western governments in Asia and Africa in the last century. Local political entities in South East Asia also experienced the same political development. Jihad concept fuelled and promoted social and political movements of Imam Diponegoro in Java, Sultan Hasanuddin in Makassar, Panglima Polem in Aceh, and Moro independence movement in Philippine. By using document analysis, depth interviews, and field observation, this study documents historical evidences that Haji Hayyun played a significant role politically and socially in Tolitoli, Sulawesi Tengah in the early twentieth century. Although tragically ended, as a figure he successfully used religious sentiment to get support from his followers against the Dutch government in Tolitoli.